BioScape: A Modeling and Simulation Language for Bacteria-Materials Interactions - Compagnoni, Adriana (2013)
We design BioScape, a concurrent language for the stochastic simulation of biological and bio-materials processes in a reactive environment in 3D space. BioScape is based on the Stochastic Pi-Calculus, and it is motivated by the need for individual-based, continuous motion, and continuous space simulation in modeling complex bacteria-materials interactions. Our driving example is a bio-triggered drug delivery system for infection-resistant medical implants. Our models in BioScape will help in identifying biological targets and materials strategies to treat biomaterials associated bacterial infections. The novel aspects of BioScape include syntactic primitives to declare the scope in space where species can move, diffusion rate, shape, and reaction distance, and an operational semantics that deals with the specifics of 3D locations, verifying reaction distance, and featuring random movement. We define a translation from BioScape to 3π and prove its soundness with respect to the operational semantics.